AN ANALYSIS OF PARENTS’ PERCEPTIONS ON THE IMPORTANCE OF HOMEWORK IN IMPROVING ENGLISH ACHIEVEMENT - Saputri, Kurnia; Larasati, Finza; Febriyani, Martina (English Community Journal, 2020)
The main purpose of this study was to identify students’ parent perceptions on the importance of homework in improving English achievement of eighth grade students at SMP Bina Bhakti Abab. The subjects of this study were all of the students’ parents of eighth grade students at SMP Bina Bhakti Abab. The study used mixed method through questionnaire as a research instrument and documentation. The questionnaire was to identify and get the information on the importance of homework for their children and the questionnaire was divided into eight points, (1) Parents’ role construction (2) Parents’ self-efficacy (3) School invitations (4) Teacher invitations (5) Child invitations (6) Parental time (7) Parental energy and (8) Parental knowledge and skills. The total of the result of each points showed that: Parents’ role construction 343 (Agree) and 287 (Strongly Agree), Parents’ self-efficacy 111 (Agree) and 99 (Strongly Agree), School invitations 32 (Disagree), 32 (Somewhat Agree) and 42 (Agree), Teacher invitations 111 (Agree) and 56 (Strongly Agree), Child invitations 33 (Agree) and 25 (Strongly Agree), Parental time 42 (Disagree) and 48 (Agree), Parental energy 24 (Disagree) and 36 (Agree), and Parental knowledge and skills 74 (Agree) and 54 (Strongly Agree).